1994
DOI: 10.1161/01.hyp.23.2.200
|View full text |Cite
|
Sign up to set email alerts
|

OPC-21268, a vasopressin V1 antagonist, produces hypotension in spontaneously hypertensive rats.

Abstract: We studied the hypotensive effects of OPC-21268, an orally effective nonpeptide vasopressin V1 receptor antagonist, in spontaneously hypertensive rats (SHR) and stroke-prone SHR (SHRSP). OPC-21268 was given intravenously to conscious, freely moving SHR and SHRSP. We used young and aged animals to examine the contribution of vasopressin to the development and maintenance of hypertension in both types of rats. In SHR, hypertension was fully established at 38 weeks of age, and intravenous injection of OPC-21268 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 25 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…of the V 2 antagonist in 16-h dehydrated rats (to stimulate vasopressin secretion) increased in volume and decreased in osmolality (<500 mosmol / l). It is noteworthy mentioning that the selectivity and the efficacy of V 1 and V 2 vasopressin antagonists in SHR, in the doses we employed in this study, were also reported by others (22,30).…”
Section: Pilotssupporting
confidence: 87%
See 2 more Smart Citations
“…of the V 2 antagonist in 16-h dehydrated rats (to stimulate vasopressin secretion) increased in volume and decreased in osmolality (<500 mosmol / l). It is noteworthy mentioning that the selectivity and the efficacy of V 1 and V 2 vasopressin antagonists in SHR, in the doses we employed in this study, were also reported by others (22,30).…”
Section: Pilotssupporting
confidence: 87%
“…It is therefore important to emphasize that the receptor subtype selectivity and the functional separation between V 1 -and V 2 -receptor blockade is warranted even at doses ten times higher than the ones we employed (22,23,28,31,50). This minimizes the possibility that the effects of vasopressin antagonists in this study were due to inhibition of receptors other than the V 1 -and V 2 -receptor subtypes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The effects of chronic blockade of the vasopressin receptors during hypertension of SHR appear controversial and the role of the V1 receptor in the pathogenesis of hypertension is unclear (51,52,55). It has been demonstrated that increased plasma vasopressin levels and enhanced binding capacity in the kidney tubules induce the decreased urine volume and increased urine osmolality (27,53) and that they play roles in the pathogenesis of hypertension by expanding effective circulating blood volume via the V2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…A hypotensive response for OPC-21268 was demonstrated in stroke-prone spontaneously hypertensive rats, suggesting a possible role of AVP in some forms of hypertension. 29 In addition, OPC-21268 improved renal function in a rat model (5/6 nephrectomized) of renal failure. 30 Significantly, the compound is orally active with an ID 50 of 2 mg/kg for inhibiting AVP-induced vasoconstriction in conscious rats and has been shown to produce drug plasma levels after oral administration to humans.…”
Section: A Avp V 1a Selective Antagonistsmentioning
confidence: 97%